Growth of the harbour porpoise (Phocoena phocoena) in eastern Newfoundland, Canada - Richardson, S F; Stenson, G B; Hood, C (NAMMCO Scientific Publications, 2003)
Although the stock relationships among harbour porpoise (Phocoena phocoena) in the NorthwestAtlantic are unknown, it has been postulated that there are 4 local populations: Bay of Fundy/Gulfof Maine, Gulf of St. Lawrence, Newfoundland, and west Greenland. Data on the Newfoundlandpopulation are extremely limited. To determine growth rates and examine if these animals can bedifferentiated from other sub-populations on the basis of growth characteristics, 94 porpoisescaught incidentally in fishing gear along the southeast coast of Newfoundland during the summersof 1990 and 1991 were examined. Most porpoises (56%) were ≤ 4 years of age. Maximumage was 9 for females and 12 for males. Growth rates were similar for both sexes until one yearof age, after which females grew longer and weighed more than males of similar ages. Using theGompertz growth model, asymptotic values for body length were 156.3 cm for females and 142.9cm for males. Asymptotic weights were 61.6 kg and 49.1 kg for females and males respectively.With the exception of West Greenland porpoise that were shorter and females from Norway thatwere lighter, Newfoundland porpoises could not be differentiated from animals collected in otherareas based on growth data. However, differences in dental deposition patterns were noted suggestingthat Newfoundland porpoise may belong to a separate population.